PENGEMBANGAN GAME EDUKASI PADA MATA PELAJARAN BIOLOGI UNTUK SISWA SMP DI KABUPATEN KUBU RAYA - Putri Novianti (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
Development of Educational Games on Biology Subjects for Junior High School Students in Kubu Raya Regency. The development of Information and Communication Technology (ICT) encourages changes in the learning process such as the use of computer-based learning media. Educational game-based learning media can be applied to Biology subjects, especially for junior high school students. This study aims to produce educational games for Biology subjects for junior high school level and to test the feasibility of the resulting educational games. The method used in this research is Research and Development (R&D) with the ADDIE development model (analysis, design, development, implementation, and evaluation). The instruments used in this research are documentation and questionnaires. The research subjects consisted of two material experts, two media experts, and thirty students of SMP N 1 Ambawang. The data analysis technique used is descriptive qualitative and quantitative data analysis. The results showed that the educational games developed were categorized as very feasible by media experts and material experts, while the responses from users of educational games were in the good category.